Androgini pada Komunitas Cross-Dresser K-Pop Dance Cover Glacies Crew - Fadhila Citra Permata; Hariyadi Hariyadi; Wiman Rizkidarajat; Arizal Mutahir (Universitas Lambung Mangkurat, 2024)
The phenomenon of androgyny in Korean pop culture (Hallyu) has garnered significant attention in Indonesia, particularly within the K-Pop Dance Cover community, which evidently incorporates the androgynous trend into cross-cover activities or imitations of K-Pop idols through cross-dressing actions. This research aims to explore how Glacies Crew, a K-Pop Dance Cover cross-dresser community based in Malang, East Java, understands and interprets gender fluidity through the androgynous trend in its performative concept, specifically in the medium of cross-dressing. This study employs a descriptive qualitative method with deep interview data collection techniques, participatory observation, and document analysis. The selection of the Glacies Crew community as the research target is determined through purposive sampling. The research findings reveal that Glacies Crew members actively engage in androgynous performativity and express gender fluidity in their daily lives. Through preparation, practice, and performance processes, community members simultaneously adopt and internalize feminine and masculine characteristics, creating diverse and dynamic gender identities. The research findings also highlight the challenges faced by community members in negotiating their gender identities within a broader society. However, the support and solidarity within the community empower members to confront these challenges. This research contributes to academic discourse on gender fluidity and non-normative gender identities in the context of Indonesian popular culture. The study underscores the importance of creating safe and inclusive spaces for individuals and developing effective interventions to reduce stigma and discrimination against individuals with non-normative gender identities.